The Flexibility of Ta'zir Punishment in the Islamic Penal System - abdul; Ali Yanda Safaruddin; Masdalena Harahap; Jia Novita Damanik; M. Syaifullah Fatwa (ISNU Sumatera Utara, 2025)
Islamic criminal law (jinayah jurisprudence) is an important instrument in upholding justice, maintaining order, and protecting the five basic principles of human life (maqasid al-syari'ah), including religion, soul, reason, offspring and property. One of the strategic elements in the Islamic punishment system is the jarimah ta'zir, which has a flexible character because it does not have standard sanctions in the Qur'an or hadith, so determining the form and level of punishment is left to the ruler or judge through the ijtihad mechanism. This research uses the literature study method (library research) by reviewing books, cutting-edge scientific works and journal articles related to the jarimah ta'zir, its legal flexibility and its relevance in dealing with contemporary crime. Descriptive-analytical analysis was carried out to describe the concept, position, flexibility and application of jarimah ta'zir in a modern context, including digital criminal acts, abuse of authority and other social violations. The results of the research show that the flexibility of the ta'zir jarimah allows judges to adjust sanctions proportionally and educatively based on the perpetrator's conditions, social impact, and the principle of substantive justice, so that Islamic criminal law remains responsive to societal dynamics. Nevertheless, the application of flexibility should be limited by the norms of the Shari'a so as not to create subjectivity and legal uncertainty. Thus, the ta'zir jarimah not only functions as a criminal tool, but also a strategic, adaptive and relevant preventive and rehabilitative instrument in the contemporary Islamic legal system, which is able to balance legal certainty, education and the benefit of society.